Calprotectin and lactoferrin faecal levels in patients with Clostridium difficile infection (CDI): a prospective cohort study. - Andrew Swale; Fabio Miyajima; Paul Roberts; Amanda Hall; Margaret Little; Mike B J Beadsworth; Nick J Beeching; Ruwanthi Kolamunnage-Dona; Chris M Parry; Munir Pirmohamed (PLoS ONE)
Measurement of both calprotectin and lactoferrin in faeces has successfully been used to discriminate between functional and inflammatory bowel conditions, but evidence is limited for Clostridium difficile infection (CDI). We prospectively recruited a cohort of 164 CDI cases and 52 controls with antibiotic-associated diarrhoea (AAD). Information on disease severity, duration of symptoms, 30-day mortality and 90-day recurrence as markers of complicated CDI were recorded. Specimens were subject to microbiological culture and PCR-ribotyping. Levels of faecal calprotectin (FC) and lactoferrin (FL) were measured by ELISA. Statistical analysis was conducted using percentile categorisation. ROC curve analysis was employed to determine optimal cut-off values. Both markers were highly correlated with each other (r2 = 0.74) and elevated in cases compared to controls (p<0.0001; ROC>0.85), although we observed a large amount of variability across both groups. The optimal case-control cut-off point was 148 mg/kg for FC and 8.1 ng/µl for FL. Median values for FL in CDI cases were significantly greater in patients suffering from severe disease compared to non-severe disease (104.6 vs. 40.1 ng/µl, p = 0.02), but were not significant for FC (969.3 vs. 512.7 mg/kg, p = 0.09). Neither marker was associated with 90-day recurrence, prolonged CDI symptoms, positive culture results and colonisation by ribotype 027. Both FC and FL distinguished between CDI cases and AAD controls. Although FL was associated with disease severity in CDI patients, this showed high inter-individual variability and was an isolated finding. Thus, FC and FL are unlikely to be useful as biomarkers of complicated CDI disease.